Indirect Decompression Using Oblique Lumbar Interbody Fusion Revision Surgery Following Previous Posterior Decompression: Comparison of Clinical and Radiologic Outcomes Between Direct and Indirect Decompression Revision Surgery - Sang-Jin Park; Jong-Moon Hwang; Dae-Chul Cho; Subum Lee; Chi Heon Kim; Inbo Han; Dae-Won Park; Heum-Dai Kwon; Kyoung-Tae Kim (Neurospine, 2022)
Objective This study compared the radiological and clinical outcomes with transforaminal lumbar interbody fusion (TLIF) to evaluate the effect of indirect decompression through oblique lumbar interbody fusion (OLIF) as revision surgery. Methods We enrolled patients who underwent single-level fusion with revision surgery at the same level as the previous decompression level. We retrospectively reviewed 25 patients who underwent OLIF from 2017 to 2018 and 25 who received TLIF from 2014 to 2018. Radiologic and clinical outcomes were evaluated by cross-sectional area (CSA) of the spinal canal, thickness and area of ligamentum flavum (LF), subsidence, disc height, fusion rate, Oswestry Disability Index (ODI), and visual analogue scale (VAS). Results Compared with OLIF, the thickness and area of the LF after surgery were significantly less in TLIF, and the resulting CSA extension was also significantly higher. However, both groups showed improvement in ODI and VAS after surgery, and there was no difference between the groups. Complications related to the posterior approach in TLIF were 4 cases, and in OLIF, there were 2 cases that underwent additional posterior decompression surgery and 6 cases of transient paresthesia. Conclusion Since complications associated with the posterior approach can be avoided, OLIF is a safer and useful minimally invasive surgery. Therefore, appropriate indications are applied, OLIF is a good alternative to TLIF when revision surgery is considered.